Jealousy and mate preferences in heterosexuals, bisexuals and homosexuals - Hromatko, Ivana (Array, 2005)
The aim of this study was to compare mate preferences and types of jealous reactions among groups of heterosexual (n=302), bisexual (n=183) and homosexual (n=133) participants. We examined the characteristics which usually show the greatest sex differences regarding their desirability in a potential mate and compared the ratings of their importance among those groups. ANOVA showed no differences between males of different sexual orientations, but there was a trend for females, with highest ratings for importance of partner's financial and social status among heterosexual, followed by bisexual and homosexual women. As for preferred age of a partner, MANOVA showed significant main effects of both age and sexual orientation in males, but only the significant effect of age in females. Contrary to some previous reports, we found no differences between males of different sexual orientations in the type of infidelity (emotional vs. sexual) they found more upsetting, but there were differences among females, with homosexual women having the highest rate of sexual jealousy responses, followed by bisexual and heterosexual women. These results suggest that men of different sexual orientations might not be so very different in their preferences, but that women are.